2005
DOI: 10.1016/j.ymthe.2005.05.014
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocytes Transduced with a Lentiviral Vector Expressing F12-vif Are Protected from HIV-1 Infection in an APOBEC3G-Independent Manner

Abstract: The viral infectivity factor (Vif) is an essential component of the HIV-1 infectious cycle. Vif counteracts the action of the cytidine deaminase APOBEC3G (AP3G), which confers nonimmune antiviral defense against HIV-1 to T lymphocytes. Disabling or interfering with the function of Vif could represent an alternative therapeutic approach to AIDS. We have expressed a natural mutant of Vif, F12-Vif, in a VSV-G-pseudotyped lentiviral vector under the Tat-inducible control of the HIV-1 LTR. Conditional expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Previous studies identified a Vif variant (F12 Vif) with dominant negative properties (51,65); however, the dominant negative effect of F12 Vif was A3G independent (51,65). This resembles our own observation of the A3G-independent inhibition of viral infectivity by high-level expression of Vif (2).…”
supporting
confidence: 84%
“…Previous studies identified a Vif variant (F12 Vif) with dominant negative properties (51,65); however, the dominant negative effect of F12 Vif was A3G independent (51,65). This resembles our own observation of the A3G-independent inhibition of viral infectivity by high-level expression of Vif (2).…”
supporting
confidence: 84%
“…Vallunti et al recently reported that F12-Vif from a nonproducer HIV-1 provirus clone F12 has anti-HIV-1 activity despite degrading A3G as efficiently as NL4-3 Vif does (46). The F12-Vif derivative Chim3-Vif is a chimera Vif generated by replacing the domain (aa 126-170) of wild-type Vif with that of F12-Vif.…”
Section: Discussionmentioning
confidence: 99%
“…25 In this configuration, eGFP is driven by the unmodified 5Ј LTR of the vector. 293T cells were seeded at a concentration of 10 5 cells/well in 24-well plastic plates (Corning Inc., New York, NY) 24 hours before transfection.…”
Section: Ltr-gfp Assaymentioning
confidence: 99%